2022
DOI: 10.3390/ijms23073605
|View full text |Cite
|
Sign up to set email alerts
|

Industrially Relevant Enzyme Cascades for Drug Synthesis and Their Ecological Assessment

Abstract: Environmentally friendly and sustainable processes for the production of active pharmaceutical ingredients (APIs) gain increasing attention. Biocatalytic synthesis routes with enzyme cascades support many stated green production principles, for example, the reduced need for solvents or the biodegradability of enzymes. Multi-enzyme reactions have even more advantages such as the shift of the equilibrium towards the product side, no intermediate isolation, and the synthesis of complex molecules in one reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Finally, although microbial lipases could be considered one of the most versatile, they alone can hardly reach the ideal goal of a predominant enzyme synthesis of an API, especially if they involve redox steps; thus, it is necessary to explore the development of enzyme cascades which include the aspects previously listed [ 236 , 237 , 238 , 239 ]. Indeed, the implementation of enzyme cascades in the synthesis of APIs with possibilities of industrial exploitation were recently reviewed [ 240 ]. Standing out in these was the synthesis of Molnupiravir for the treatment of COVID-19, where the immobilized CAL B lipase (Novozym ® 435) participates.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…Finally, although microbial lipases could be considered one of the most versatile, they alone can hardly reach the ideal goal of a predominant enzyme synthesis of an API, especially if they involve redox steps; thus, it is necessary to explore the development of enzyme cascades which include the aspects previously listed [ 236 , 237 , 238 , 239 ]. Indeed, the implementation of enzyme cascades in the synthesis of APIs with possibilities of industrial exploitation were recently reviewed [ 240 ]. Standing out in these was the synthesis of Molnupiravir for the treatment of COVID-19, where the immobilized CAL B lipase (Novozym ® 435) participates.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…The interest in in vitro enzyme cascades has increased in recent decades and more and more attempts on cascade assemblies are performed [19]. Applications cover a broad field from the synthesis of complex high value compounds such as natural products or active pharmaceutical ingredients to bulk chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this microorganism-based approach allows to modify starting molecules exploiting several advantages over chemical synthesis, such as the regio- and/or stereospecificity of the reactions. Despite the exciting advantages, only a few biotransformation-based approaches have been applied in the pharmaceutical industry so far [ 20 ]. A recent study reported the production of two new steroid compounds (coded SCA and SCB), not chemically synthesizable, by the biotransformation of cortisone [ 15 ].…”
Section: Discussionmentioning
confidence: 99%